(untitled) (Journal of research in medical and health sciences, 2026)
Objective: To analyze the treatment process of a patient with postherpetic neuralgia and explore the advantages of acupuncture at Jiaji (EX-B2) points combined with moxibustion using moxa cones in the treatment of postherpetic neuralgia. Methods: One case of postherpetic neuralgia was reported. The patient was treated with acupuncture at Jiaji (EX-B2) points combined with moxibustion using moxa cones, and the therapeutic outcome was analyzed and discussed. Results: After 4 weeks of treatment, the patient’s pain was markedly relieved and sleep returned to normal. Conclusion: Acupuncture at Jiaji (EX-B2) points combined with moxibustion using moxa cones showed a significant therapeutic effect in the treatment of postherpetic neuralgia and is worthy of clinical promotion. More importantly, treatment should be initiated as early as possible at the onset of the disease so as to actively prevent the occurrence of postherpetic neuralgia.